The effect of the practical competency management process of the human resource in achieving overall efficient performance in light of the knowledge economy (Case of Food Industry Institutions in Northeastern Algeria) - Rouibi, Samir; Mecheri, Mohamed Nacer (International journal of economic perspectives, 2024)
The study aims to clarify the Impact of competency management process in attainment of Overall performance efficiency in food industry institutions in northeastern of Algeria until it elevate to the requirements of the knowledge age, and until we get the expected results from the study, a questioner was distributed for 87 institutions for the purpose of collecting and analyze data by using SPSS 24 program and has been recovered 71 questioner, with 80,61 percent of recovered, where the descriptive analytical method was used to cover the theoretical aspect of study and the field study was used to extrapolate and analyze factual data. The results of statistical analysis showed that there is a medium Impact of competency management more precisely the dimension of competency development in the institutional performance but it does not elevate into the challenges of the modern era, which is why food industry institutions in northeastern of Algeria must adopt modern management practices specially the competency management process.